Phototherapy on Management of Creatine Kinase Activity in General Versus Localized Exercise: A Systematic Review and Meta-Analysis - Machado, Aryane Flauzino [UNESP]; Micheletti, Jessica Kirsch [UNESP]; Lopes, Jaqueline Santos Silva [UNESP]; Vanderlei, Franciele Marques [UNESP]; Leal-Junior, Ernesto Cesar Pinto; Netto Junior, Jayme [UNESP]; Pastre, Carlos Marcelo [UNESP] (Lippincott Williams & Wilkins, 2020)
Objective: The main focus of this systematic review was to determine the efficacy of phototherapy in the management of creatine kinase (CK) activity after exercise and furthermore to identify for which exercise model protocol phototherapy provides the best results. Design: Meta-analysis comparing phototherapy with a control condition. Setting: The MEDLINE, EMBASE, SPORTDiscus, PEDro, and CENTRAL databases were searched from their earliest records to October 03, 2016. Data were pooled in a meta-analysis and described as standardized mean difference (SMD) with 95% confidence intervals (CIs) using a random effects model. Participants: Healthy subjects (no restrictions were applied, eg, age, sex, and exercise level). Intervention: Phototherapy (low-level laser therapy and/or light-emitting diode therapy) before or after exercise and a placebo or control condition. Main Outcome Measures: Creatine kinase activity (no restriction to any analysis, eg, serum, plasma, or capillary blood). Results: Fourteen studies were included for review. The results revealed that phototherapy has a more positive effect than control condition in management of CK activity [SMD = 0.77, 95% CI (0.32 to 1.22); P = 0.0007; I-2 = 72%]. In exploratory analysis, the results showed that phototherapy was effective only in the exercise protocol with localized exercise with large effect size [localized exercise: SMD = 0.89, 95% CI (0.26 to 1.51); P = 0.0002; I-2 = 76%; general exercise: SMD = 0.61, 95% CI (-0.05 to 1.26); P = 0.07; I-2 = 67%]. Conclusions: The available evidence suggest that phototherapy has beneficial effects on the management of CK activity and demonstrate a possible relationship based on damage caused by exercise, providing a greater effect in studies that used localized exercise.
Keywords: phototherapy; recovery of function; athletic performance; creatine kinase